Type A aortic dissection after abdominal aortic surgery - Murtaza A Chishti; Vijay Mohan Hanjoora; Monish S Raut; Ashish Sharma (Heart and Mind, 2020)
Aortic dissection after open surgical repair of infrarenal aortic aneurysm and after endovascular procedures is a rarely observed complication. We present one such interesting case where vigilant monitoring plays an important role to diagnose aortic dissection early and subsequently manage successfully.